2018
DOI: 10.1136/bcr-2018-224419
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukaemia relapse presenting as cardiac myeloid sarcoma

Abstract: A 50-year-old woman previously diagnosed with acute myeloid leukaemia presented with a 3-month history of shortness of breath and a right-sided facial rash. A chest CT revealed an intracardiac mass in the right atrium extending into her superior and inferior vena cava. Surgery was performed to remove the mass and pathology was consistent with myeloid sarcoma. After surgery, adjuvant radiation therapy was directed to the residual disease. The patient eventually relapsed in other sites not including the right at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“… 10 Isolated cardiac relapse after allogeneic peripheral blood HSCT is rarely reported, with only scattered cases in the literature, mostly presenting as solid myeloid sarcoma or myocardial hypertrophy and constrictive cardiac physiology. 11 13 The patient in this case presented with an isolated cardiac effusion without evidence of myeloid sarcoma or involvement outside the cardiovascular system during her first IEMR. In some studies, it was reported that IEMR has a better prognosis than bone marrow relapse, 7 , 9 which seems consistent with our case.…”
Section: Discussionmentioning
confidence: 92%
“… 10 Isolated cardiac relapse after allogeneic peripheral blood HSCT is rarely reported, with only scattered cases in the literature, mostly presenting as solid myeloid sarcoma or myocardial hypertrophy and constrictive cardiac physiology. 11 13 The patient in this case presented with an isolated cardiac effusion without evidence of myeloid sarcoma or involvement outside the cardiovascular system during her first IEMR. In some studies, it was reported that IEMR has a better prognosis than bone marrow relapse, 7 , 9 which seems consistent with our case.…”
Section: Discussionmentioning
confidence: 92%